A Review on Measurement of Spectral Directional Emissivity of Microstructured Surfaces in Infrared Wavelength Range - Koirala, Lila Raj (KEC Journal of Science and Engineering, 2023)
A survey of researches in the field of spectral directional emissivity measurements of microstructured surfaces by using direct and indirect radiometric methods in infrared wavelength range is presented. Nowadays, new concepts of periodic surface microstructures with geometrical dimensions of the same order of magnitude as the thermal radiation wavelengths are becoming one of the attractive methods for controlling spectral radiative properties of a surface like emissivity and reflectivity. Since the resonance effect between the periodic microstructures and the electromagnetic field has become one of the most promising ways to vary optical or radiative properties of the radiating surfaces artificially, in this review paper emphasis is given to the measurement of directional spectral emissivity of microstructured surfaces. A review of many systems is presented that are capable of measuring the spectral directional emissivities of solid surfaces at moderate temperatures. An overview of experimental setups is provided including the reference sources of radiation, the sample clamping and heating, detection systems, methods for the determination of surface temperature and procedures for emissivity evaluation. The paper is focused on methods of finding the emissivity of microstructures. Selected experimental data in the form of graph are presented for various microstructured surfaces.